(untitled) (European Journal of Behavioral Sciences, 2019)
In the context of anthropological understanding for mature, self-updating personality the moral and legal culture is an essential element. Personality with the high level of the moral and legal culture is able to integrate in his mind and behavior some moral and legal norms, to create mindset according to these norms, to express and assert himself, to strive to transform the surrounding not destroying it, it is ready to act in the framework of freedom and responsibility. High social expectations for the moral and legal upbringing of the younger generation make new demands on the teacher and it necessitates the creation of the moral and legal culture at the university education. It was developed the model of the educational process at the pedagogical university in our research.